‘I didn’t know if it was illegal for her to talk about my religion in a job interview’: Young Muslim Women’s Experiences of Religious Racism in Australia - Imtoual, Alia ca. 20./21. Jh. (Journal for the academic study of religion, 2006)
Muslim women in Australia, as in many other majority non-Muslim countries, have experienced unprecedented levels of hostility and negativity over the last few years. These experiences have been described by the term ‘islamophobia’, a word that was coined in the mid-1990s in Britain and that has gained significant purchase in the British literature particularly. This term has not had the same level of influence in Australia, although its usage is becoming more popular despite some criticisms of its definition and application. This article discusses and develops these critiques and offers religious racism as an alternative term. It offers a critique of existing South Australian and Commonwealth anti-racism and anti-discrimination legislation and argues that, although there appears to be broad bureaucratic recognition of the existence of religious racism, the legislation does not protect Muslims in South Australia from such racism based on religious affiliation. This article also draws upon narratives told by young Muslim women in South Australia to illustrate not only the nature and pervasiveness of the racism they experience, but also the complete lack of protection for these women under existing legal frameworks.